Studi Analisis terhadap Tafsir Al-Munir Karya Prof. Dr. Wahbah Zuhaily - Hermansyah Hermansyah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Tafseer Al Munir by Prof. Dr. Wahbah Zhuhaily are amongst the best commentary on the book of the modern age. Book this interpretation has some advantages from various sides including the most good interpretation, kindest systematic discussion, and the most excellent and easy to understand language. We are hard to find it in the book of classical interpretations. The most predominant method used is the method of analytic interpretation / tahlili, with shades of a merger between tafsir bi al-ma'tsur with commentary ar bi-ra`y. It's just that the author failed to give us an insight kekininian in his commentary, but nevertheless these shortcomings only slightly and did not affect kecermalangan commentaries in this modern age